Evidencia parasitol6gica sobre la fdogenia de los homínidos y los cébidos - Retana Salazar, Axel P (Revista de Biología Tropical, 1996)
A systematic revision of the ectoparasites (lice) of the hominoids and ceboids supports the Trogloditian hypothesis, according to which .the genus Homo is the sister group of Pan, and the genus Gorilla the sister group of both. The phylogenetic analysis of this matrix derived from the study of primate lice shows an C.I. of 0 .71 for the Trogloditian hypothesis including the ceboids in the analisis